Prevalence and associated factors of modern contraceptive discontinuation among sexually active married women in Nigeria - J. A. Kupoluyi; B. L. Solanke; O. M. Adetutu; J. O. Abe (BMC, 2023)
Abstract Background Contraceptive discontinuation for reasons other than the desire for pregnancy is associated with a high rate of unintended pregnancies leading to unsafe abortions, maternal morbidity and mortality. In Nigeria, little is known about modern contraceptive discontinuation using the calendar data. Methods A cross-sectional research design from the 2018 Nigeria Demographic and Health Surveys (NDHS) women's dataset was used to examine the prevalence and associated factors of modern contraceptive discontinuation among sexually active married women in Nigeria. A weighted sample size of 3,353 currently sexually active married or in union women who have ever used a modern contraceptive 5 years before the survey and with complete reproductive histories and are not sterilised or declared infecund was analysed. Data were analysed and displayed using frequency tables and charts, chi-square test, and binary logistic regression model at 5% level of significance. Results The prevalence of modern contraceptive discontinuation was 35.8% (1199) with 45.8% (549) of the women discontinuing using modern contraceptives while at risk of pregnancy. The most modern method discontinued was Injectables (25.2%) while the commonest reason for modern method discontinuation was because they wanted to become pregnant (36.1%). Associated factors of modern contraceptive discontinuation among sexually active married women in Nigeria were: marital duration (aOR = 3.0; 95%CI: 1.5-6.2), visitation to a health facility in the last 12 months before the survey (aOR = 0.6; 95%CI: 0.4-0.8), education (aOR = 2.0; 95%CI: 1.2-3.4) and region of residence (aOR = 2.7; 95%CI: 1.6-4.7). Conclusion Modern contraceptive discontinuation among the study respondents was high. Region of residence, health facility visitation and marital duration were significantly associated with modern contraceptive discontinuation. The study suggests that health care providers should address the discontinuation of contraception through counselling, particularly among women who reside in the region of high prevalence of contraceptive discontinuation, short-term users as well as strengthen the use of contraception among those who are still at risk of becoming pregnant. Governments and stakeholders should also partner with private sectors to make health care accessible to women by bring health facilities closer to them to improve facility visitation.